Market Structure, International Competitiveness, and Price Formation of Hainan's Fruit Exports. (24th March 2021) - Fu, Hailing; Huang, Chongli; Teng, Zhuoqi; Fang, Yuantao
Abstract : Through a constant market share (CMS) model and a price index model, current research aims to analyze the impetus of the growth of Hainan, China's fruit exports and the adverse impact of rising production costs. This paper considered the changes in the international competitiveness of Hainan's fruit exports and analyzed the reasons for these changes. Additionally, this manuscript analyzed the effects of Hainan's price-bargaining power on fruit exports under the condition of asymmetric information by applying a two-tier stochastic frontier analysis model. The results show that the rising costs of labor led to the gradual loss of price advantage, and the contribution of competitiveness to the growth of Hainan's fruit exports has rapidly declined. The results also indicate that the degree of information held by both importers and Hainan has an important influence on the final exporting price, whereas the importers hold more information and have stronger price-bargaining power than Hainan. Policy suggestions based on the results are proposed.